Advancements and Challenges Forensic Odontology and Anthropology: Applications for Identification in Saudi Arabia (The International Journal for Scientific Research, 2024)
The evolution of forensic science has witnessed significant progress in dental identification techniques, originating from prehistoric eras but gaining prominence in the late 19th century. During the 1960s, forensic odontology experienced renewed interest, extending its relevance beyond dentistry to law enforcement agencies. This resurgence coincided with the emergence of forensic anthropology, vital in employing skeletal analysis to reconstruct the biological profiles of unidentified individuals. Collaborative efforts of forensic dentistry and anthropology have notably enhanced the accuracy and scope of forensic investigations, especially in cases involving incomplete or decomposed remains. In the Kingdom of Saudi Arabia, despite cultural challenges, the significance of multidisciplinary collaboration to assist the law enforcement agencies cannot be overstated. As forensic science advances, the integration of dental and skeletal analyses remains crucial for effective case resolution. Forensic odontology and anthropology jointly contribute to identifying individuals in mass disasters and criminal cases through dental record and skeletal remains analysis. Both disciplines boast rich historical backgrounds, dating back to ancient civilizations. Limited practices and training in Saudi Arabia pose obstacles for forensic investigations, although there is evident public acceptance regarding the importance of maintaining dental records and recognizing skeletal analysis significance. Therefore, establishing a national registry for dental and skeletal data, coupled with comprehensive training programs, is recommended for dentistry and anthropology students at all academic levels.
Keywords: Forensic Science; Identification; Forensic Odontology; Forensic Anthropology; Skeletal Analysis